Prevalence of Major Dermatovenereological Diseases in Uzbekistan - Abdusalomovich, Boltayev Nodirjon; Nayim qizi, Ne`matova Roziya; Fozil qizi, Mamatova El’mira (American Journal of Bioscience and Clinical Integrity, 2025)
This study investigates the clinical and epidemiological characteristics of gallbladder diseases, focusing primarily on cholelithiasis. It examines the effectiveness of surgical interventions—especially comparing laparoscopic cholecystectomy with traditional open surgery—in treating both typical and acute presentations. The research draws on clinical data from 150 patients treated between 2022 and 2024, incorporating medical history, lab diagnostics, imaging, and surgical outcomes. Findings indicate that laparoscopic surgery significantly reduces postoperative complications and accelerates patient recovery, making it the preferred option for most cases. In contrast, open surgery remains relevant for complex or emergency scenarios. This research fills a gap in localized clinical data for Uzbekistan and emphasizes the need for improved surgical service quality and preventive health measures. The results support broader adoption of minimally invasive techniques and reinforce the importance of timely intervention in acute cases.